Cognitive Assessment of Health-Care Workers Exposed to Ionizing Radiation and The Assessment of Radiation Safety Awareness in Different Radiation Oncology Hospitals in Egypt - Saleh, Basma M. (AUC Knowledge Fountain, 2023)
The increase in cancer cases and subsequent increase in chemotherapy and radiotherapy sparked worries over hospital workers' health and safety. There is a global trend towards routine assessment of awareness, safety measures, and radiation protection culture among healthcare workers. There is also a trend towards monitoring the various associations between radiation exposure and different health outcomes. In low- and middle-income countries, the use of advanced techniques and biomarker tests to track the health status of the workers is hard to achieve. This is due to the scarce resources and economic instabilities and that is why using a survey as a primary indicator may be of great value. There has been no published research into what Egyptian healthcare workers exposed to radiation know, whether they are following radiation exposure safety practices, and to what extent they may be affected by this occupational exposure. Recent evidence suggests that low-dose ionizing radiation exposure to the brain may function as a therapeutic technique for fighting neurodegenerative illnesses such as Alzheimer's, and this can be used as a way to track radiation exposure effects based on a simple cognitive assessment test. This is of great importance given the increase in radiation oncology units in Egypt. A gap analysis is done using an easy self-evaluation survey to assess Egyptian healthcare workers’ awareness of radiation safety practices a long with their cognitive function. A few short-structured interviews were done with radiation protection specialists at some hospitals. Besides that, an additional assessment of the cognitive function status to study the effect of radiation exposure on cognitive ability. Our findings showed that there is a huge gap in the awareness of healthcare workers dealing with radiation regarding radiation protection techniques across the four hospitals chosen in this study in Egypt. There is a need for giving more attention to investments in healthcare workers' training, retention, and support. The results alert policymakers now to invest in bridging the gap of radiation safety knowledge and implementing hospital based, national based, and international based plans and collaborations. Our findings also suggest that there is there is some, but very limited, evidence of the impact of radiation exposure on cognitive function. In order to increase knowledge of radiation-induced cognitive consequences, research in larger epidemiological cohorts and experimental investigations in relevant models with more documented readings about the dose of radiation exposure are required. Our findings also support the idea of investing in building the cognitive reserve by improving educational qualifications in order to have better cognitive performance among individuals.